Film-immobilized carbon nitride for the degradation of pharmaceuticals: A continuous flow photoreactor performance upheld by excitation-emission matrix fluorescence spectroscopy. - Peñas-Garzón, Manuel; Sampaio, María José; Chávez, Ana María; Silva, Adrián M.T.; Silva, Cláudia G.; Faria, Joaquim L. (Elsevier, 2024)
The validation of immobilized photocatalysts is a fundamental matter regarding the scaling-up process in the photocatalytic degradation of aqueous pollutants in natural surface waters. This work presents the comprehensive evaluation of graphitic carbon nitride (g-C3N4, CN) immobilized onto a polymeric film (F) placed inside a continuous flow operation planar reactor for the removal of a mixture of pharmaceuticals (i.e., venlafaxine, citalopram, carbamazepine, tramadol, ketoprofen, and diclofenac, 3 μM each) under visible light. The resulting CN/F (8 mg of CN per cm2 of film and with significant preservation of optical and structural properties after more than 350 h of reuse) yielded the complete removal under total recirculation of all pharmaceuticals after 90 min under visible light, except for ketoprofen, probably ascribed to competition for photogenerated holes, as suggested by the proposed mechanism. Under dead-end continuous flow mode, the steady-state conversion averaged 67% in deionized water, increasing up to 76%, and 80% in natural surface waters obtained from the Douro River and the effluent from a wastewater treatment plant (Northwestern Portugal), respectively, related to the promotion effect of carbonates anions and organic matter. The assessment of excitation-emission matrix (EEM) fluorescence spectroscopy coupled with parallel factor (PARAFAC) analysis further demonstrated the removal (ca. 50%) of the protein- and humic-like substances contained in the collected wastewater, thus evidencing the continuous flow mode performance of the immobilized photocatalyst for real environmental applications.
Keywords: Fotocatálisis; Nitruros; Espectroscopia de fluorescencia; Graphitic carbon nitride; Supported photocatalyst; Wastewater treatment; Continuous flow operation; EEM-PARAFAC